Gunmetal black - Serrano, Daniel; Copyright paperback collection (Library of Congress) (New York : Grand Central Pub., 2011)
Tired of the street life, ex-con Eddie Santiago has one simple, strictly legitimate dream: to head for Miami and start his own salsa record label. But two dirty cops have confiscated Eddie's life savings and an old-school thug who helped Eddie in the past now wants more than simple payback. And Eddie's friend Tony needs help eliminating a rival drug dealer and planning a casino heist that's anything but a sure bet. Soon Eddie is wanted for murder, under the gun, and running out of time.
Previously issued as a trade pbk.
'Winner of the international Latino award for best popular fiction'--Cover.
Keywords: Detective and mystery stories; Chicago (Ill.) -- Fiction